2009
DOI: 10.1007/s12020-009-9211-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical effects of calcifediol supplementation in mild, asymptomatic, hyperparathyroidism with concomitant vitamin D deficiency

Abstract: It has been proposed to cautiously supplement with vitamin D to any patient with asymptomatic primary hyperparathyroidism (PHTP) and a plasma 25-hydroxyvitamin D [25(OH)D] concentration <50 nmol/l. Evidence about the safeness of this intervention is limited to two studies. Our aim was to prospectively assess the biochemical effects of one-year 25(OH)D supplementation in this context. Twenty-seven patients were included in this study. Calcifediol was started at a dose of 480-960 IU/24 h (8-16 microg/24 h) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…Tucci (67) could not substantiate any risk of vitamin D 2 treatment in PHPT at doses up to 2500 mg/month. Plasma creatinine levels and the occurrence of renal stones were not reported in these studies (65)(66)(67)(68).…”
Section: Safetymentioning
confidence: 77%
See 1 more Smart Citation
“…Tucci (67) could not substantiate any risk of vitamin D 2 treatment in PHPT at doses up to 2500 mg/month. Plasma creatinine levels and the occurrence of renal stones were not reported in these studies (65)(66)(67)(68).…”
Section: Safetymentioning
confidence: 77%
“…However, the decrease was no longer significant after 1 year of treatment (19.7G14.2 vs 17.2G14.6 pmol/l, NS). Average plasma calcium levels remained unchanged at 3 months (2.70G0.13 mmol/l), 6 months (2.73G 0.10 mmol/l) and 12 months (73G0.10 mmol/l) (68).…”
Section: The Preoperative Lowering Of Plasma Pthmentioning
confidence: 92%
“…18 Several other studies in comparable patient groups with PHPT and vitamin D deficiency have similarly reported stable calcium concentrations with or without an increase in urinary calcium in response to various doses of vitamin D supplements. 17,25 More recently, Wagner et al 19 assigned patients to treatment with either 1000-2000 IU daily or 50,000 IU weekly of vitamin D. PTH concentrations were unchanged in both groups and calcium concentrations remained stable in the high dose group but decreased in the low dose group although this became statistically insignificant after multiple adjustments for age, sex, vitamin D, and PTH concentrations. Lastly, Ranganathan et al also showed that in postmenopausal female with PHPT and coexisting vitamin D deficiency prolonged treatment with vitamin D reduced serum PTH concentration with no adverse effects on adjusted serum calcium concentrations and renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available on the effect of vitamin D repletion in PHPT patients; increase in urinary calcium excretion has been reported, though with no evidence of kidney stones development (20,21,22). A recent interventional study in PHPT patients with coexistent vitamin D deficiency showed that vitamin D replacement increases serum 25-hydroxyvitamin D levels and reduces serum PTH without causing hypercalcaemia and hypercalciuria (23).…”
Section: Effects Of Cholecalciferol Supplementation On Hypercalciuriamentioning
confidence: 99%